ANALYSIS OF THE CAPABILITY OF PAI TEACHERS IN THE IMPLEMENTATION OF SOCIAL AND CULTURAL LITERACY ACTIONS IN MIS SYABABUL QORIB - Sya'bana, Dzul Fadli; Nurmawati, Nurmawati; Nasution, Sahkholid (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2024)
This research aims to analyze the ability of Islamic Education teachers in implementing the Indonesian Madrasah Competency Assessment (AKMI) for socio-cultural literacy at MIS Syababul Qorib. The research was conducted using a qualitative method through observations and interviews. The results indicate that the ability of Islamic Education teachers to implement AKMI for socio-cultural literacy, in general, is not yet optimal, considering aspects such as understanding of concepts, teaching methods and media, as well as assessment techniques. The main constraints identified are time limitations and a lack of training. Therefore, continuous training and mentoring for teachers, improvement of infrastructure, and regular monitoring and evaluation by the madrasah authorities are necessary. Comprehensive capacity building for Islamic Education teachers is crucial to optimize the implementation of AKMI and enhance the socio-cultural literacy competence of students.